2019
DOI: 10.1177/0956797618820626
|View full text |Cite
|
Sign up to set email alerts
|

When the Muses Strike: Creative Ideas of Physicists and Writers Routinely Occur During Mind Wandering

Abstract: How often are creative ideas generated during episodes of mind wandering, and do they differ from those generated while on task? In two studies ( N = 98, N = 87), professional writers and physicists reported on their most creative idea of the day, what they were thinking about and doing when it occurred, whether the idea felt like an “aha” moment, and the quality of the idea. Participants reported that one fifth of their most significant ideas of the day were formed during spontaneous task-independent mind wan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 15 publications
(16 reference statements)
3
80
2
2
Order By: Relevance
“…However, mind wandering can also be used as a mental break when one is trying to solve a problem. A number of experiments have shown that people who are stumped in solving certain kinds of problems are subsequently much more likely to solve the problem if they think about something else (engaged in mind wandering) [40]. We argue that this relationship is curve-linear, mind wandering can have a negative effect on cognitive absorption to a point it turns positive and helps an individual engage in an activity.…”
Section: Mind Wandering and Cognitive Absorptionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, mind wandering can also be used as a mental break when one is trying to solve a problem. A number of experiments have shown that people who are stumped in solving certain kinds of problems are subsequently much more likely to solve the problem if they think about something else (engaged in mind wandering) [40]. We argue that this relationship is curve-linear, mind wandering can have a negative effect on cognitive absorption to a point it turns positive and helps an individual engage in an activity.…”
Section: Mind Wandering and Cognitive Absorptionmentioning
confidence: 73%
“…The findings reveal that when mind wandering reaches a certain point, it may increase accessibility to the problem at hand. This increased accessibility may serve as a functional role by enabling novel ideas to spring in mind [50], yielding positive affect that marks the realization of successful relevant processing [47].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…It is assumed that both spontaneous and controlled processes are relevant to creative cognition (Beaty, Silvia, Nusbaum, Jauk, & Benedek, 2014; for reviews, see Benedek & Jauk, 2018;Chrysikou, 2018). On the one hand, there is robust evidence that higher executive capacity predicts higher creative task performance (Benedek, Jauk, Sommer, Arendasy, & Neubauer, 2014;Silvia, 2015), but on the other hand, creativity is sometimes found to benefit from states of reduced control (e.g., Benedek, Panzierer, Jauk, & Neubauer, 2017;Gable, Hopper, & Schooler, 2019;Radel, Davranche, Fournier, & Dietrich, 2015). This may be related to the ambiguous role of task-irrelevant information for creative thought: Looking at distractor pictures could have triggered spontaneous autobiographical or semantic memories (Faber & D'Mello, 2018), which may sometimes have promoted performance by inspiring novel associations for possible uses and sometimes may have hampered performance by simply interrupting the ongoing internal train of thought.…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter are: Enstrangement-any displacement or odd juxtaposition of unrelated verbal or visual elements that violates logical expectations and familiar associations; Spoiled drawings, using the wrong (nondominant) hand; Puzzles/riddles/counterfactuals or nonsensically framed short narratives, sparking novel solutions or meaning-making; and Exquisite Corpse-a collaborative game of blind (folded-paper) composition in images or words, exploiting the creative potential of chance and the collective unconscious (Rosen 2014). Playful activities like these can disrupt rigid, consciously controlled thinking, allowing fixed ideas to ebb in favor of the divergent/ flexible/ creative cognition of Mind Wandering (Smallwood & Schooler 2015;Rosen 2016;Gable et al 2019). A productive form of unconscious nonlinear processing (also known as stimulus-independent thought), this fluid neurocognitive state occurs when attention turns away from external tasks toward more remote internal, personally meaningful thought and spontaneous generation of ideas.…”
Section: Iii) Observe Closelymentioning
confidence: 99%